The Effect of the Knisley Mathematical Learning Model with the Assistance of the GeoGebra Application on the Mathematical Problem Solving Ability of Class XI Students of SMA Negeri 1 Batang Kuiz - Julita Elis Listiawaty; Erlinawaty Simanjutak (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to find out whether or not there is an effect of the Knisley mathematics learning model with the help of the GeoGebra application on the mathematical problem solving abilities of class XI students of SMA Negeri 1 Batang Kuis. Based on the results of research and data processing, the following conclusions can be obtained: from the calculation results of the hypothesis test, it is obtained that tcount = 7.719 and ttable = 1.671, it is obtained that tcount > ttable which means that H_0 is rejected and H_a is accepted. So, it can be concluded that there is an influence from the Knisley mathematics learning model with the help of the GeoGebra application on the mathematical problem solving abilities of class XI students of SMA Negeri 1 Batang Quiz